2021
DOI: 10.1080/10803548.2021.2007660
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of work interventions to promote safe patient handling and movement in the healthcare sector

Abstract: Objectives. The aim of this systematic review was to describe interventions which promote safe patient handling and movement (PHM) among workers in healthcare by reviewing the literature on their effectiveness for work and health-related outcomes. Methods. Databases were searched for studies published during 1997-2018. Measures were operationalized broadly, capturing outcomes of work and health. Only randomized controlled trials (RCTs) and cohort studies with a control group were included. Quality was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…The identification of problems in the organization of work is the basis for the development of workplace health interventions and participatory ergonomics programs. These programs have been applied in different contexts, with encouraging results [ 76 , 77 ]. It is, however, evident that programs can only work with the concrete support of company management [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…The identification of problems in the organization of work is the basis for the development of workplace health interventions and participatory ergonomics programs. These programs have been applied in different contexts, with encouraging results [ 76 , 77 ]. It is, however, evident that programs can only work with the concrete support of company management [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other promising strategies for safe PHM were participatory ergonomics, joint management and HCW engagement. 14 However, further knowledge into how to develop a combination of workplace interventions, including risk assessments, is needed to further facilitate safe PHM and prevent musculoskeletal disorders. The intervention strategies that will be evaluated in this study are based on regulations for occupational safety and health, clinical guidelines and previous research into interventions that promote safe PHM.…”
Section: Introductionmentioning
confidence: 99%
“…This implies a need to further focus on combining risk assessments for patients and HCWs to prevent and eliminate risks and promote a healthy, safe and sustainable healthcare environment. The importance of performing risk assessments as a basis for choosing interventions is supported by laws and regulations as well as previous research 13 14…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of interventions and safe patient handling programs in reducing care provider injuries in clinical care facilities, such as hospitals and nursing homes, is well studied. 16,17 However, the efficacy of these same preventative measures in the home health care setting is not well understood. 18 Research has found differences between HBHC providers and those in clinical care facilities with regard to the types of injuries suffered, injury rates, demographics and chronic health conditions.…”
Section: Introductionmentioning
confidence: 99%